2021
DOI: 10.1111/acel.13372
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory KIR+RA+ T cells accumulate with age and are highly activated during viral respiratory disease

Abstract: Severe respiratory viral infectious diseases such as influenza and COVID‐19 especially affect the older population. This is partly ascribed to diminished CD8+ T‐cell responses a result of aging. The phenotypical diversity of the CD8+ T‐cell population has made it difficult to identify the impact of aging on CD8+ T‐cell subsets associated with diminished CD8+ T‐cell responses. Here we identify a novel human CD8+ T‐cell subset characterized by expression of Killer‐cell Immunoglobulin‐like Receptors (KIR+) and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
(106 reference statements)
0
15
0
Order By: Relevance
“…Mechanisms within this category include NK cell interactions with dendritic cells which subsequently affect T cell responses during priming (14), NK killing of activated CD4 + and CD8 + T cells (10)(11)(12) and suppression of T cells by a recently-described population of iKIR-expressing regulatory CD8 + T cells (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms within this category include NK cell interactions with dendritic cells which subsequently affect T cell responses during priming (14), NK killing of activated CD4 + and CD8 + T cells (10)(11)(12) and suppression of T cells by a recently-described population of iKIR-expressing regulatory CD8 + T cells (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…For example, during SARS-CoV-2, 151,152 Influenza B, 152 or Seasonal coronavirus, 152 the frequency of T cells within CD4 + and CD8 + compartments that express CD57 and KIR or EMRA and inflammation increase significantly in the lungs compared to uninfected individuals.…”
Section: The Possible Role Of Senescent T Cells In Different Human Di...mentioning
confidence: 99%
“…Moreover, TVM cells have been shown to contribute to the control of HIV-infected CD4 + T cells in humans, likely through KIR-mediated interactions and killing of infected cells ( 101 ). Furthermore, our group has recently shown that KIR-expressing TVM cells accumulate in the blood with progressing age and are capable of suppressing proliferation of other CD8 + T cells ( 102 ). Based on these findings, TVM cells may also be considered a type of suppressive CD8 + T-cell subset, although their role at early age remains to be elucidated.…”
Section: Tolerance By T Cells At Early Agementioning
confidence: 99%